2020
DOI: 10.1186/s43019-020-00078-9
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental knee arthroplasty and revision total knee arthroplasty have a lower risk of venous thromboembolism disease at 30 days than primary total knee arthroplasty

Abstract: Background While multiple studies have demonstrated a lower venous thromboembolism disease (VTED) risk for unicompartmental knee arthroplasty (UKA) compared to primary total knee arthroplasty (TKA), recent reports have shown that revision TKA also had a lower VTED risk compared to primary TKA, an unexpected finding because of its theoretical increased risk. Given the paucity of up-to-date comparative studies, our goal was to perform a high-powered VTED risk comparison study of UKA and revision TKA to primary T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Ogonda et al 22 analyzed data from the National Joint Registry for England and Wales and found a 1.2% PE rate after UKA, while the Humana database has demonstrated a PE rate of 0.8% after UKA. 2,22 Schneider et al 30 assessed that same database as the present study, without applying an age limit in the UKA group, and found a lower PE rate (0.2%) after UKA. The results of the current study align with the findings by Schneider et al and suggest that even though PE is an infrequent complication, prophylaxis should be considered to avoid devastating consequences.…”
Section: Discussionsupporting
confidence: 55%
“…Ogonda et al 22 analyzed data from the National Joint Registry for England and Wales and found a 1.2% PE rate after UKA, while the Humana database has demonstrated a PE rate of 0.8% after UKA. 2,22 Schneider et al 30 assessed that same database as the present study, without applying an age limit in the UKA group, and found a lower PE rate (0.2%) after UKA. The results of the current study align with the findings by Schneider et al and suggest that even though PE is an infrequent complication, prophylaxis should be considered to avoid devastating consequences.…”
Section: Discussionsupporting
confidence: 55%
“…By contrast, the rate of DVT in patients underwent osteotomies around the knee was exceedingly high, postoperative DVT was detected in 11.9% knees after open wedge high tibial osteotomy and 22.6% in later closed wedge high tibial osteotomy respectively [ 6 ]. As for VTEs after joint arthroplasty surgery, incidence of DVT ranges from 0.4 to 42% [ 7 , 8 ], occurrence of DVT of lower extremity following knee arthroplasty, especially the UKA surgery, is lower than that of hip arthroplasty. In our clinical practice, patients were encouraged to perform ankle pump exercise on the day after operation, meanwhile, pneumatic therapy was also introduced to promote lower limb blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…We found no significant difference between the two surgeries in most complication rates, meanwhile, significant differences were found in the incidence of DVT and surgical site infection. The HTO group showed significantly low infection rate, which may be related to a relatively short operation time [ 22 24 ] and showed low risk of DVT possibly due to routine usage of mechanical compression after surgery [ 25 ], and pharmacologic prophylaxis [ 26 ]. There have been previous studies on factors related to ARF after orthopedic surgery, but studies related to different surgical methods, especially artificial joint surgery, have been insufficient and may require further evaluation [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%